Open-loop hover experiment of a Mach-scaled SNUF rotor for active vibration control - Im, B.; Ryi, J.; Rhee, W.; Lee, H.; Kong, K.; De Poitevin, C.; Dhin, S.J. (My University, 2022)
Design and open-loop hover experiment of a 4-blade Mach-scaled Seoul National University Flap (SNUF) rotor equipped with an active trailing-edge flap is attempted. Its test is performed on the Seoul National University Rotor Test Stand (SNURTS). First, the rotor hub is improved to withstand the centrifugal loads. In it, the original soft in-plane hingeless rotor hub used for blade optimal design is replaced by a rigid hingeless rotor hub. The multi-body dynamic analysis DYMORE and cross-sectional design tool VABS are used to design the new rotor hub adaptor for the flap blade by utilizing time-marching free-wake analysis. Preliminary hover test using two-bladed OLS teetering hub showed excellent repeatability of the SNURTS, but a torque level of 400N-m should be considered. Rotor test stand modal test response and servo kinematics are fully adjusted into the analysis model. Next, a single active flap blade test is performed to assess the flap driving component. The hysteresis of the flap driving mechanism is identified in a static bench test. Bench dynamic tests of the SNUF blade active flap showed that present flap actuation system has 4/rev bandwidth. In the future, flap deflections will be recorded for the 1-5/rev at 1300 RPM, where the tip Mach number is 0.6. The frequency response of the flap mechanism will be identified under hover centrifugal loads while the blades are still in-track.